Klebsiella pneumoniae: a multidrug-resistant pathogen, has emerged in Saudi Arabia - Aldali, Jehad A. (Frontiers in Microbiology, 2025)
Klebsiella pneumoniae (K. pneumoniae), a significant opportunistic pathogen, has developed resistance mechanisms to numerous antimicrobials, including carbapenems. This article evaluates the prevalence, risk factors, antimicrobial susceptibility and resistance mechanisms of K. pneumoniae across various locations in Saudi Arabia. Hospital-acquired infections attributed to K. pneumoniae are prevalent in the country due to several factors, including the high incidence of critically ill patients, frequent gastrointestinal colonization and the extensive use of antimicrobial agents. The prevalence of K. pneumoniae strains resistant to multiple antimicrobials, including carbapenems, has risen. Hospitals facilitate the proliferation of multidrug-resistant (MDR) K. pneumoniae due to the extensive utilization of broad-spectrum antibiotics, the likelihood of interpatient transmission, the elevated risk of infection during invasive procedures in intensive care units and the frequent occurrence of invasive diagnostic and therapeutic interventions among diabetic and cancer patients. Combinations of colistin and tigecycline with carbapenems or other antibiotics remain the optimal treatment for patients with MDR K. pneumoniae infections, despite the increasing prevalence of resistance to these agents noted in numerous hospitals. The high incidence of MDR K. pneumoniae in Saudi hospitals necessitates comprehensive investigation into the molecular mechanisms underlying multidrug resistance. A thorough understanding of K. pneumoniae resistance patterns and the formulation of a treatment protocol to mitigate the infection burden in Saudi Arabia could be enhanced by establishing a local antibiogram database.